Micro Optical Coherence Tomography for Coronary Imaging - Nishimiya, Kensuke; Tearney, Guillermo (Frontiers in Cardiovascular Medicine, 2021)
Intravascular optical coherence tomography (IVOCT) that produces images with 10 μm resolution has emerged as a significant technology for evaluating coronary architectural morphology. Yet, many features that are relevant to coronary plaque pathogenesis can only be seen at the cellular level. This issue has motivated the development of a next-generation form of OCT imaging that offers higher resolution. One such technology that we review here is termed micro-OCT (μOCT) that enables the assessment of the cellular and subcellular morphology of human coronary atherosclerotic plaques. This chapter reviews recent advances and ongoing works regarding μOCT in the field of cardiology. This new technology has the potential to provide researchers and clinicians with a tool to better understand the natural history of coronary atherosclerosis, increase plaque progression prediction capabilities, and better assess the vessel healing process after revascularization therapy.